Synthesis of multi-type rare earth compounds with RE(OH)SO4 as a new sacrificial-template and photoluminescence. Issue 3 (3rd July 2022) - Wang, Xuejiao; Feng, Xiaowen; Sun, Meng; Wang, Bowen; Wang, Jiantong; Li, Ji-Guang
ABSTRACT: The low OH − /RE 3+ molar ratio of hydroxide sulfate RE(OH)SO4 (RE = rare earth) makes it a potential good template for the synthesis of rare earth compounds, which is shown in this work by the direct generation of (La, Eu)F3, (La, Eu)PO4, Na(La, Eu)(WO4 )2, and Na(La, Eu)(MoO4 )2 without further calcination. The template showed irregular and slightly aggregated micro-plates morphology, while the products derived from the template showed morphologies of nanoparticles (trifluoride), nanorods (phosphate), aggregate spheres (molybdate), and aggregated polyhedrons (tungstate). The photoluminescence of the derived compounds, including excitation/emission spectra, decay kinetics, quantum yields, color coordinates, and color purities were comprehensively investigated, and the results were well correlated with structures and morphologies. Calcination further improved the luminescence intensity and quantum yield of the obtained phosphors. It is believed that the RE(OH)SO4 compound proposed in this work may find applications for the synthesis of other rare earth compounds.